Anti-inflammatory effect a specific Lactiplantibacillus plantarum in an Ovalbumin-induced asthma model - Kishida, Shigefumi; Kato-Mori, Yuko; Okamoto, Minoru; Hagiwara, Katsuro (Microbiology and immunology, 2022)
Autoimmune, allergic, and respiratory inflammatory diseases are some of the most important health issues worldwide. Disorders of the gut microbiota have been associated with the induction of allergic and inflammatory diseases, and probiotics are being tested for disease prevention. We examined functional Lactiplantibacillus plantarum RGU (Lp-1) to mice with ovalbumin-induced asthma model to elucidate the inhibitory effect on pathological progression in asthma model. Prior to the experiments, the intestinal lactic acid bacteria were reduced by administering multiple antibiotics (MAB) to evaluate the administration effect of lactic acid bacteria. Mice were administered with Lp-1 or comparative control lactic acid bacteria in each group. After that, OVA-induced asthma was induced, and cytokine gene expression and histological findings were compared. Exacerbation of lung lesions was confirmed in the MAB group. The Lp-1 group mice had alleviated lung lesions with a decrease in IL1β, IL13, IL17 and an increase in IL10 of the splenocytes and bronchial lymph nodes compared to the MAB group, but not in the other groups. In OVA-induced asthma, administration of specific Lactiplantibacillus was confirmed to induce anti-inflammatory cytokines. This article is protected by copyright. All rights reserved.